Globalization and terror in Africa - Simplice Asongu; Nicholas Biekpe (African Governance and Development Institute (AGDI), 2017)
This study examines the role of globalization on terrorism in 51 African countries for the period 1996-2011. Four terrorism indicators are used, namely: domestic, transnational, unclear and total terrorism. Political, economic, social and general globalisation variables are employed and the empirical evidence is based on Fixed Effects regressions and Generalised Method of Moments (GMM). Whereas the FE regressions are overwhelmingly not significant, the following findings are established from GMM estimations. Political globalisation increases both domestic and transnational terrorism. Social globalisation and general globalisation increase transnational terrorism. Economic globalisation reduces domestic terrorism. Political globalisation, social globalisation and general globalization positively affect unclear terrorism. Social globalisation has a positive impact on total terrorism. Possible channels and policy implications are discussed.
Keywords: C52; D74; F30; F42; O55; 330; Terrorism; Globalization; Africa